Partial Order in Environmental Sciences and Chemistry - Brüggemann, Rainer; Carlsen, Lars (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Partial Order? - Never heard of it! This comment will be heard no more, when the broadness of this mathematical concept has been explained. Many internationally renowned authors assist the reader in understanding what partial order is and where, why and how this concept can be used. Since all the authors have teaching experience, partial order is explained step by step. Mathematical formalism is avoided as far as ever possible. The book begins with some basics, considers applications in different fields and ends with some historical notes. After reading this book, the comment should become: Partial order! - Where is the next book?